2022
DOI: 10.3390/cells12010113
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Islet Cells Response to IFNγ Relies on Their Spatial Location within an Islet

Abstract: Type 1 diabetes (T1D) is an auto-immune disease characterized by the progressive destruction of insulin-producing pancreatic beta cells. While beta cells are the target of the immune attack, the other islet endocrine cells, namely the alpha and delta cells, can also be affected by the inflammatory milieu. Here, using a flow cytometry-based strategy, we compared the impact of IFNγ, one of the main cytokines involved in T1D, on the three endocrine cell subsets isolated from C57BL/6 mouse islets. RNA-seq analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Cytokines and ER stress are reported triggers of PDL1 (also known as CD274) expression in beta cells, which occurs in type 1 diabetes [37]. Non-diabetic beta cells do not express PDL1, unlike beta cells from donors with type 1 diabetes, and the expression levels correlate with higher chemokine expression and immune cell-beta cell interaction [37][38][39]. We found that cytokines induced the expression of PDL1 in islets (Fig.…”
Section: Cb1r Blockade Ameliorates the Atf6 Arm Of The Unfolded Prote...mentioning
confidence: 80%
“…Cytokines and ER stress are reported triggers of PDL1 (also known as CD274) expression in beta cells, which occurs in type 1 diabetes [37]. Non-diabetic beta cells do not express PDL1, unlike beta cells from donors with type 1 diabetes, and the expression levels correlate with higher chemokine expression and immune cell-beta cell interaction [37][38][39]. We found that cytokines induced the expression of PDL1 in islets (Fig.…”
Section: Cb1r Blockade Ameliorates the Atf6 Arm Of The Unfolded Prote...mentioning
confidence: 80%